Exploring the Culture of Surveillance: A Qualitative Study in Portugal - Faustino, Délcio; Simões, Maria João (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
By following the theoretical framework of the surveillance culture this article aims to detail the surveillance imaginaries and practices that individuals have, capturing differences and social inequalities among respondents. We present an in-depth look into surveillance awareness, exploring subjective meanings and the varying awareness regarding commercial, governmental, and lateral surveillance. Furthermore, a detailed analysis is made on how individuals sometimes welcome surveillance, expanding on the cost-benefit trade-off, and detailing it on three distinct trade-offs: the privacy vs. commercial gains/rewards, the privacy vs. convenience and, the privacy vs. security. Lastly, we present a section that explores and analyzes resistance to surveillance.